Prospective experimental study of transrectal viscerotomy closure using transanal endoscopic suture vs. circular stapler: a step toward NOTES - Diana, M.; Leroy, J.; Wall, J.; De Ruijter, V.; Lindner, V.; Dhumane, P.; Mutter, D.; Marescaux, J. (Endoscopy, 2012)
Background and study aim: Endoluminal full-thickness closure of the rectal wall is critical in emerging procedures including endoscopic submucosal dissection and transrectal natural orifice transluminal endoscopic surgery (NOTES). This study aimed to compare manual suture using the transanal endoscopic operation platform (TEO; Karl Storz, Tüttlingen, Germany) with the end-to-end anastomosis hemorrhoid circular stapler (EEA; Covidien, Dublin, Ireland) for closure of the rectal viscerotomy during transrectal NOTES segmental colectomy.Materials and methods: A total of 12 swine underwent transrectal hybrid NOTES partial colectomies. Animals were divided into two groups according to the viscerotomy closure technique: 1) TEO manual suture; 2) EEA circular stapler closure. Results: Mean (± SD) viscerotomy closure time was 67.5 ± 59.5 minutes and 31.5 ± 19.6 minutes for TEO and EEA, respectively. There was one conversion to laparoscopy in the TEO group and a misfiring in the EEA group that required a TEO salvage suture. There was one positive air-leak test in each group. Peritoneal fluid collected at the end of the procedure tested positive for bacterial contamination in all cases. A mild stenosis was present in 4 /6 viscerotomies (67 %) in the TEO group and in 1/6 (17 %) in the EEA group on endoscopic control. Inflammatory changes were mild in 3/5 (60 %) and 4/5 (80 %) viscerotomies in the TEO and EEA groups, respectively, whereas severe inflammation was found in 2/5 (TEO) and 1 /5 (EEA).Conclusion: Transrectal viscerotomy closure using the EEA circular stapler technique is feasible, easy to perform, and histologically comparable to suture closure through a TEO platform. It may offer an attractive alternative for NOTES segmental colectomies and endoscopic resections.